Development of an Absence System using IoT Technology Based on Radio Frequency Identification (RFID) - Hutagalung, Nur Aini (Yayasan Kita Menulis, 2026)
SMK Negeri 1 Rambang Niru has implemented an online attendance system, but it still faces challenges related to reliability, accuracy, and efficiency, as the system is not based on Internet of Things (IoT) technology. This research aims to develop an automated attendance system utilizing IoT technology based on Radio Frequency Identification (RFID) to improve the effectiveness and efficiency of attendance tracking. The system uses RFID tags assigned to teachers and administrative staff , which are scanned by an RFID reader connected to a microcontroller. Once detected, the attendance data is immediately transmitted to a centralized server via an IoT communication module. The approach involves integrating RFID hardware with IoT infrastructure, as well as developing software for database management and user interface. The system was tested in the SMK Negeri 1 Rambang Niru work environment to evaluate scanning accuracy, response time, and data consistency. The results show that the RFID-based attendance system provides high reliability, fast data processing, and minimizes errors. This implementation demonstrates the potential to replace the existing online attendance system, enhancing data integrity and providing an efficient solution in modern workplace environments.